1996
DOI: 10.1074/jbc.271.15.8661
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the DNA Polymerase -Primase B Subunit Is Dependent on Its Association with the p180 Polypeptide

Abstract: The B subunit of the DNA polymerase (pol) ␣-primase complex executes an essential role at the initial stage of DNA replication in Saccharomyces cerevisiae and is phosphorylated in a cell cycle-dependent manner. In this report, we show that the four subunits of the yeast DNA polymerase ␣-primase complex are assembled throughout the cell cycle, and physical association between newly synthesized pol ␣ (p180) and unphosphorylated B subunit (p86) occurs very rapidly. Therefore, B subunit phosphorylation does not ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 33 publications
1
28
0
Order By: Relevance
“…The phosphorylation of pol α/primase has been reported in human and S. cerevisiae cells (38)(39)(40); both human p180 and p70 were phosphorylated predominantly during late G2 and M phases of the cell cycle (38). Yeast p86 (B subunit) is phosphorylated in a manner that depends on the stage of the cell cycle (39), but most phosphorylation occurs late in the cell cycle, suggesting that it might play a role either in coordinating replication and mitosis or in resetting the replication apparatus for the next S phase.…”
Section: Dna Polymerase α/Primase Complexmentioning
confidence: 99%
“…The phosphorylation of pol α/primase has been reported in human and S. cerevisiae cells (38)(39)(40); both human p180 and p70 were phosphorylated predominantly during late G2 and M phases of the cell cycle (38). Yeast p86 (B subunit) is phosphorylated in a manner that depends on the stage of the cell cycle (39), but most phosphorylation occurs late in the cell cycle, suggesting that it might play a role either in coordinating replication and mitosis or in resetting the replication apparatus for the next S phase.…”
Section: Dna Polymerase α/Primase Complexmentioning
confidence: 99%
“…T antigen, RP-A, and DNA polymerase a-primase, that are required for initiation of SV40 DNA replication, are potential substrates of Cyclin-dependent kinases (Cdks; Dutta and Stillman 1992;McVey et al, 1989;Nasheuer et al, 1991Nasheuer et al, , 1992. Since RP-A and DNA polymerase a-primase are key cellular replication proteins, and they are phosphorylated in a cell cycle-dependent manner, it was suggested that their phosphorylation might be important for the regulation of DNA replication (Din et al, 1990;Dutta and Stillman 1992;Ferrari et al, 1996;Foiani et al, 1995;Nasheuer et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was reported that p68 specifically plays an essential role at the initial stage of DNA synthesis, before the hydroxyurea-sensitive step, and that the subunit is phosphorylated and dephosphorylated in a cell cycle-dependent manner (11,12). Furthermore, formation of the p180-p68 subcomplex appears to be a prerequisite for p68 phosphorylation (10). However, the physiological role of p68 phosphorylation has been refractory to investigation.…”
mentioning
confidence: 99%